2013
DOI: 10.1590/s1413-70542013000600001
|View full text |Cite
|
Sign up to set email alerts
|

Employing conformational analysis in the molecular modeling of agrochemicals: insights on QSAR parameters of 2,4-D

Abstract: A common practice to compute ligand conformations of compounds with various degrees of freedom to be used in molecular modeling (QSAR and docking studies) is to perform a conformational distribution based on repeated random sampling, such as Monte-Carlo methods. Further calculations are often required. This short review describes some methods used for conformational analysis and the implications of using selected conformations in QSAR. A case study is developed for 2,4-dichlorophenoxyacetic acid (2,4-D), a wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The color system employed is the RGB (24 bits ); therefore, the pixels can assume values that varies from “0” (black color) to 765 (white color), since each pixel in this system is a result of the combination of three color channels (red, green, and blue) and each of these channels assumes values that vary from 0 to 255. These considerations have shown satisfactory outcomes, often comparable to those results obtained using 3D methodologies (Daré, Barigye, & Freitas, ; de Freitas & Ramalho, ; Freitas et al., ; Guimarães et al., ). Moreover, MIA‐QSAR also includes a graphical tool denominated MIA‐plot that allows the user to obtain a detailed chemical interpretation of the regression models (Barigye, Duarte, Nunes, & Freitas, ; Borges & Barigye, ).…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…The color system employed is the RGB (24 bits ); therefore, the pixels can assume values that varies from “0” (black color) to 765 (white color), since each pixel in this system is a result of the combination of three color channels (red, green, and blue) and each of these channels assumes values that vary from 0 to 255. These considerations have shown satisfactory outcomes, often comparable to those results obtained using 3D methodologies (Daré, Barigye, & Freitas, ; de Freitas & Ramalho, ; Freitas et al., ; Guimarães et al., ). Moreover, MIA‐QSAR also includes a graphical tool denominated MIA‐plot that allows the user to obtain a detailed chemical interpretation of the regression models (Barigye, Duarte, Nunes, & Freitas, ; Borges & Barigye, ).…”
Section: Introductionsupporting
confidence: 70%
“…The main advantages of this approach are (a) the parameters (descriptors) contain simple and efficient information of the molecular structure, (b) they are also invariant to molecule roto‐translations, and, finally, (c) these parameters can be obtained avoiding geometry optimization (Consonni & Todeschini, ). On the other hand, the 2D models, although reliable, are not easily interpretable in a meaningful way, that is, it is not always possible to find a biochemical/physicochemical explanation for the propriety under analysis based on the QSAR model (de Freitas & Ramalho, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…for the herbicide 2,4-D, whose bioactive conformation is different from that of the free compound [13], 2 can be useful to probe for the rule of intramolecular interactions on the bioactive conformation of molecules. Indeed, both diphenhydramine molecules complexed in the crystal histamine methyltransferase enzyme (PDB code: 2AOT, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the protonated diphenhydramine was experimentally and theoretically studied to give insight about the role of the electrostatic gauche effect in this cation, and also because it is not explicit in the crystal if the bioactive compound is protonated or not [12]. The outcomes from this study can be useful to understand the role of intramolecular interactions as governing factors of the conformational preferences in a biological environment, since an earlier work showed that the bioactive conformation of 2,4-dichlorophenoxyacetic acid (2,4-D), an herbicide that binds the TIR1 ubiquitin ligase enzyme, does not match the structure of the calculated most stable conformer [13].…”
Section: Introductionmentioning
confidence: 98%